The Relationship Between Spirituality, Health-Related Behavior, and Psychological Well-Being - Bożek, Agnieszka; Nowak, Paweł F.; Blukacz, Mateusz (Frontiers in Psychology, 2020)
Studies suggest a positive association of spirituality and health behaviors with well-being (especially subjective), but still little has been known about the relationships between all these constructs. The present study aims to explore the relations between spirituality, health-related behaviors, and psychological well-being in the context of acquired education. A questionnaire survey was conducted on a group of 595 students from six different universities whose study programs either focused on the human body, or the human mind and spirit. Path analysis and linear regression were used to model the relationship between the examined constructs. The results show that both spirituality and health-related behaviors are positively related to psychological well-being, and that the relationship with spirituality is also mediated by health-related behaviors. Only spirituality is associated with the type of acquired education, especially in the group of students whose studies focus on the human mind and spirit. Moreover, spirituality in this group seems to have a stronger relation with psychological well-being. These findings may contribute to the better understanding of some significant determinants of psychological well-being. They carry important implications for the faculty members responsible for curriculum preparation to account for teaching contents related to the conduct of a healthy lifestyle and spiritual development.